A Novel Fiber-1-Edited and Highly Attenuated Recombinant Serotype 4 Fowl Adenovirus Confers Efficient Protection Against Lethal Challenge - Yaru Mu (Frontiers Media S.A., 2021)
Currently, a fatal disease of hepatitis-hydropericardium syndrome (HHS) caused by serotype 4 fowl adenovirus (FAdV-4) has spread worldwide and resulted in tremendous economic losses to the poultry industry. Various vaccines against FAdV-4 were developed to control the disease; however, few live-attenuated vaccines were available. In this study, we targeted the N-terminal of fiber-1 and rescued a recombinant virus FAdV4-RFP_F1 expressing the fusion protein of RFP and Fiber-1 based on the CRISPR/Cas9 technique. In vitro studies showed that FAdV4-RFP_F1 replicated slower than the wild type FAdV-4, but the peak viral titer of FAdV4-RFP_F1 could still reach 107.0 TCID50/ml with high stability in LMH cells. Animal studies found that FAdV4-RFP_F1 not only was highly attenuated to the 2-week-old SPF chickens, but could also provide efficient protection against lethal challenge of FAdV-4. All these demonstrate that the recombinant virus FAdV4-RFP_F1 could be as an efficient live-attenuated vaccine candidate for FAdV-4, and the N-terminal of fiber-1 could be as a potential insertion site for expressing foreign genes to develop FAdV-4-based vaccine.